2010
DOI: 10.1007/s12564-010-9097-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting organizational commitment from organizational culture in Turkish primary schools

Abstract: This study aims to describe organizational culture and commitment and to predict organizational commitment from organizational culture in Turkish primary schools. Organizational Culture Scale ( _ Ipek 1999) and Organizational Commitment Scale (Balay 2000) were used in the data gathering process. The data were collected from 415 primary teachers and analyzed to describe their organizational culture and organizational commitment perceptions by computing arithmetic means for each dimension constituting these scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Bogler and Nir (2015) found that perceived organisational support positively explained variance in teachers' OC. Ipek's (2010) analysis of school culture dimensions indicated that support culture positively predicted both teachers' AC and NC. Nayir (2012) reported that supervisor support emerged as a strong predictor of teachers' NC, and Shapira-Lishchinsky and Rosenblatt (2009, 2010) described how a caring climate was associated with teachers' AC and NC.…”
Section: Inspiring Visionmentioning
confidence: 98%
“…Bogler and Nir (2015) found that perceived organisational support positively explained variance in teachers' OC. Ipek's (2010) analysis of school culture dimensions indicated that support culture positively predicted both teachers' AC and NC. Nayir (2012) reported that supervisor support emerged as a strong predictor of teachers' NC, and Shapira-Lishchinsky and Rosenblatt (2009, 2010) described how a caring climate was associated with teachers' AC and NC.…”
Section: Inspiring Visionmentioning
confidence: 98%
“…Teachers' job satisfaction (Gligorović, Nikolić, Terek, Glušac, & Ivan Tasić, 2016) (Kılınç, 2014). School culture is also significant for performance (Karadağ, 2009) and teachers' organizational commitment (İpek, 2010;Ayık & Ataş, 2014). It is a determinant between effective and ineffective schools (Schoen & Teddlie, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Organizational culture has a critical relationship with teacher motivation because it determines the way in which teachers behave and perform (Ipek, 2010). However, the analysis of the relationship between school organizational culture and teacher motivation must be addressed meticulously, because different cultures have distinct effects on teacher motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational culture refers to the set of shared values and assumptions that determine a teacher's behaviour (Ipek, 2010;Schneider et al, 2013). Negis-Isik and Gursel (2013) found that organizational culture was fundamental to a school's success and that it significantly affected teacher satisfaction and motivation.…”
mentioning
confidence: 99%